The impact of elevated water nitrate concentration on physiology, growth and feed intake of African catfish Clarias gariepinus (Burchell 1822). Issue 9 (14th December 2012) - Schram, Edward; Roques, Jonathan A C; Abbink, Wout; Yokohama, Yanick; Spanings, Tom; de Vries, Pepijn; Bierman, Stijn; van de Vis, Hans; Flik, Gert
Abstract The nitrate threshold concentration in rearing water of African catfish (Clarias gariepinus) was assessed. Female African catfish with an initial mean (SD) weight of 154.3 (7.5) g were exposed to 0.4 (Control), 1.5, 4.2, 9.7 and 27.0 mM nitrate for 42 days. Mean (SD) plasma concentrations of nitrate increased from 71 (29) to 6623 (921) μM at the highest ambient nitrate level. Mean (SD) plasma nitrite concentration ranged from 1.2 (0.5) to 7.9 (9.0) μM. Haematocrit, plasma concentrations of non‐esterified fatty acids (NEFA), cortisol, glucose, lactate, osmolality, gill morphology and branchial Na+/K+‐ATPase activity were not affected. Feed intake and specific growth rate were significantly reduced at the highest nitrate concentration. We advise not to exceed a water nitrate concentration of 10 mM (140 mg L−1 NO3‐N) to prevent the risk of reduced growth and feed intake in African catfish aquaculture.